2022
DOI: 10.3389/fspor.2022.1018752
|View full text |Cite
|
Sign up to set email alerts
|

The perception of injury risk and prevention among football players: A systematic review

Abstract: Football is associated with a certain risk of injury, leading to short- and long-term health consequences. However, the perception of football players about injury risk and prevention strategies is poorly documented. The present article reviewed the literature about perceptions, beliefs, attitudes and knowledge toward injury risk and prevention strategies in football players. An electronic search was performed in PubMed, Scopus, Web of Science, and APA PsychINFO until July 2022. Studies were eligible if they i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…the players could make a reasonable estimation of their risk of injury. This contrasts with previous research suggesting that perception of low injury risk could be associated with a risk-taking behaviour [8] and thus make the player more prone to injury. Only 29% of the players (male and female) in the present cohort believed it was likely that they would sustain an injury during the season (1-3 on the Likert scale).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…the players could make a reasonable estimation of their risk of injury. This contrasts with previous research suggesting that perception of low injury risk could be associated with a risk-taking behaviour [8] and thus make the player more prone to injury. Only 29% of the players (male and female) in the present cohort believed it was likely that they would sustain an injury during the season (1-3 on the Likert scale).…”
Section: Discussioncontrasting
confidence: 99%
“…Only 29% of the players (male and female) in the present cohort believed it was likely that they would sustain an injury during the season (1–3 on the Likert scale). This is considerably lower compared to a recent systematic review that reported that most football players believed that their risk of sustaining an injury was moderate to high, and players expected to sustain at least one injury over the course of the following season [8]. Also, compared to players’ expectations at the beginning of the season, where 29% of players believed it was likely that they would sustain an injury during the season, the injury burden was substantially higher, as 130 male players reported a total of 95 injuries, and the 332 female players reported a total of 350 injuries during the season.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Muscle strength plays a crucial role in joint flexibility and stability and is an essential component of fatigue recovery programs [ 32 ]. In this study, isometric muscle strength tests were conducted at 60°/s and 180°/s angular velocities.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is a multifactorial health problem in which risk factors are often in cause-andeffect relationships, studies have highlighted several clear risk factors [16,17]. Some of these factors such as age, previous injuries, and surface conditions cannot be controlled [18,19]. On the other hand, a player's range of motion, muscle strength and flexibility, physical fitness, and mechanical load imposed on players are things that coaches can and must take care of [16,17].…”
Section: Introductionmentioning
confidence: 99%